Hospital finances, service quality in hospital care and the Indonesian national health insurance system - Firda Nur Laila; Vip Paramarta; Farida Yulianty; Kosasih Kosasih; Afira Febriani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Indonesia’s National Health Insurance (NHI) program represents a significant step toward achieving Universal Health Coverage (UHC). While it has successfully broadened healthcare access, the program faces considerable challenges regarding financial sustainability, which directly affects hospital operations and service quality. Purpose: To assess the impact of NHI implementation on hospital financial performance and service quality in Indonesia, identify influencing factors, and offer strategic policy recommendations. Method: A systematic literature review was conducted using the PRISMA protocol. Relevant studies published between January 2020 and February 2025 were sourced from five major databases (PubMed, Scopus, Web of Science, ScienceDirect, and ISJD). Articles were selected based on rigorous inclusion and exclusion criteria and analyzed thematically. Results: Following the introduction of the NHI program, many hospitals encountered financial strain, mainly due to delayed claim reimbursements and reimbursement rates considered inadequate. These financial constraints led to reduced investment in workforce development, medical technology, and infrastructure. A positive link was identified between hospital financial health and the quality of care delivered. Conclusion: The future success of the NHI program is highly dependent on its ability to ensure both the financial viability of hospitals and the delivery of high-quality healthcare. A failure to maintain this balance may undermine the broader health system's effectiveness. Suggestions: A cohesive policy approach is essential, involving collaboration among the Social Security Administering Body for Health, healthcare providers, and the government. This includes establishing fair reimbursement rates, expediting claim processes, and supporting hospitals in maintaining and enhancing service quality.